﻿﻿Calcium and vitamin D metabolism in sarcoidosis - ﻿Baughman, R.P.; ﻿Janovcik, J.; Ray, M.; Sweiss, N.; Lower, E.E. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Background: Sarcoidosis associated hypercalcemia (SAHC) may be secondary to excessive levels of 1,25-(OH)2 vitamin D3 produced by autonomous 1-alpha-hydroxylase activity within the granulomas. The frequency, treatment, and consequences of hypercalcemia remain unclear. Study Design and Methods: Two patient cohorts were studied. In Cohort 1, the prevalence of hypercalcemia in 1606 sarcoidosis patients seen during a six year period was analyzed along with treatment and outcome. Cohort 2 consisted of 261 sarcoidosis patients with measured 25-(OH) vitamin D3 and 1,25-(OH) vitamin D3 levels. In forty patients, serial levels of 25-(OH) vitamin D3 and 1,25-(OH) vitamin D3 were measured at least three months apart without change in therapy. Results: SAHC was identified in 97 of 1606 (6%) of patients studied and additional nine (0.6%) patients had primary hyperparathyroidism. Post treatment follow up was available in 86 SAHC patients. Hypercalcemia improved in >90% of patients, including eight patients treated solely with vitamin D supplement withdrawal. Renal insufficiency, documented in 41 (42%) of SAHC patients, improved with hypercalcemia treatment. In 80% of Cohort 2 patients low 25-(OH) vitamin D3 levels were measured with only one patient having a low 1,25(OH)2 vitamin D3 level. Elevated 1,25(OH)2 vitamin D3 levels, which were measured in 11% of patients, were higher for those with a history of hypercalcemia. Conclusion: Sarcoidosis associated hypercalcemia, which is often accompanied by renal insufficiency, responds to treatment of sarcoidosis and withdrawal of vitamin D supplementation. Measurement of serum vitamin 1,25(OH)2 vitamin D3 appears to best evaluate vitamin D status in sarcoidosis patients.